Window Dressing Phenomenon on LQ45 Stock Investment Decisions with a Modern Technical Analysis Approach - Deby Dewanty Daulay (Formosa Journal of Applied Sciences, 2023)
The anomalous phenomenon of the windows dressing market has the potential to distort stock prices amidst the issue of an economic recession which is predicted to occur in 2023. This research aims to analyze the trend of LQ45 index stock price movements amidst the windows dressing phenomenon. This type of research is descriptive with a qualitative approach using secondary data. The research subjects are the Top 5 Constituents on the LQ45 Fact Sheet as of September 2023 published by the BEI. The object of the research is graphic data and monthly stock price movement trends for 5 issuers in the fourth quarter starting from October-December 2023. The data is analyzed using a modern technical analysis approach using the Relative Strength Index and Bollinger Band indicators via the tradingview.com website. The research results show a weakening of the short-term share price trend for LQ45 index issuers, which is likely due to a temporary correction, while the long-term fundamental prospects for several issuers are still positive.